PERANAN STATISTIK DALAM BIDANG AKUNTANSI (PENDEKATAN TEKNIK SAMPLING AUDIT OLEH AUDITOR) - Aziz, Abdul; Dimyati, Novika; Wiguna, M. Wisnu Kusuma; Irianto, Bambang Setyobudi (Jurnal Riset Akuntansi Soedirman, 2023)
This paper explains the role of statistics in the field of accounting, especially the approach to audit sampling techniques by auditors. There are two sample sizes through the application of a statistical and non-statistical based formula. The application of a statistical-based sample size was carried out using a random selection method with the help of the Ms application. Excel (Index Formula, Rand Formula, and Rank Formula) applied to the "random item" data group. Meanwhile, non-statistical based sample size is applied to the "quantitative item" and "qualitative item" data groups. The sampling process was carried out on 1,011 inventory data with an inventory value of Rp. 7,502,701,074,-. The results show that the combination of applying sample sizes based on statistics "random selection" and non-statistics "qualitative and quantitative items" is able to produce a sample size of 66% of the total population of data tested.